The effect of supplementation of Lactobacillus paracasei HII01 on salivary cortisol, and dehydroepiandrosterone sulfate (DHEA-S) levels - Lalitsuradej, Ekasit; Sivamaruthi, Bhagavathi Sundaram; Sirilun, Sasithorn; Sittiprapaporn, Phakkharawat; Peerajan, Sartjin; Chaiyasut, Chaiyavat (Asian Journal of Medical Sciences, 2020)
Background of the study: Fatigue is one of the serious health issues, and stress is the main factor that induces chronic fatigue syndrome (CFS). The dysregulation of stress management pathway may account for the development of CFS. The human body comprises several neurobiological networks to manage physical and emotional insults. Hypothalamic-pituitary- adrenal (HPA) axis is one of the important neuroendocrine networks involved in the neurophysiological activity of the host system. The response of HPA axis depends on the physical and psychological state of stress and other factors like time and duration of stress. The probiotic supplements are proved as an adjuvant therapeutic agent for several diseases. Aims and Objective: The aim of the current study was to evaluate the effect of Lactobacillus paracasei HII01 supplementation on salivary cortisol and DHEA-S levels of fatigue subjects. Materials and Methods: After 12-weeks of probiotic intervention significantly reduced the salivary cortisol level, while DHEA-S level was not affected. The ratio of cortisol: DHEA-S was reduced after probiotic intervention. Results: The results concluded that L. paracasei HII01 has the ability to reduce the stress level in fatigue subjects by reducing the salivary cortisol level. Conclusion: The results evidently to recommend that the ingestion of 12.5 billion cells of L. paracasei HII01 per day for 12 weeks significantly amended HPA-Axis by lowering salivary cortisol and ratio cortisol: DHEA-S in fatigue subjects.